Analytical and Numerical Deflection Study on the Structure of 10 kW Low Speed Permanent Magnet Generator - Hilman Syaeful Alam; Pudji Irasari; Dyah Kusuma Dewi (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
Analytical and numerical studies of the deflection in the structure of 10 kW low speed permanent magnet generator (PMG) have been discussed in this paper. This study is intended to prevent failure of the structure when the prototype is made. Numerical analysis was performed with the finite-element method (FEM). Flux density, weight and temperature of the components are the required input parameters. Deflection observed were the movements of the two main rotor components, namely the rim and shaft, where the maximum deflection allowed at the air gap between rotor and stator should be between 10% to 20% of the air gap clearance or 0.1000 mm to 0.2000 mm. Base on the analysis, total deflection of the analytic calculation was 0.0553 mm, and numerical simulation was 0.0314 mm. Both values were in the acceptable level because it was still below the maximum allowed deflection. These results indicate that the structure of a permanent magnet generator (rim and shaft) can be used safely.